Sanksi Pidana Bagi Pelaku Kejahatan Sekstorsi Dalam Hukum Positif Di Indonesia - I Nyoman Krisna Hermawan; A.A Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2025)
The development of period advanced brings a variety of implications, both constructive and destructive. Cybercrime often takes the form of online sexual orientation-based violence, namely sexual crimes with the threat of spreading pornographic content. The formulation of the problem in this research is 1) Regulation of sex offenders in Indonesian positive law 2) Criminal sanctions against sex offenders, this research uses normative legal research. The legal regulation of sexortion cases in Indonesia can be viewed from the provisions contained in the Criminal Code as lex generalis as well as provisions outside the Criminal Code. In September 2019, a video titled "Vina Garut" went viral on social media. A video of trio sexual intercourse (sexual intercourse performed by three people simultaneously) with V as one of the actors in it surfaced on social media. R - V's husband, who claimed to have separated from V, forced V to have sexual intercourse, R also recorded the sexual intercourse and sold it on Twitter. V, R and another actor, WW, were questioned by Garut Police.